2011
DOI: 10.1103/physrevb.84.184435
|View full text |Cite
|
Sign up to set email alerts
|

Spiral magnetic structure in spin-52frustrated trimerized chains in SrMn3P4Oet al.

Abstract: We study a spin-5/2 antiferromagnetic trimerized chain substance SrMn 3 P 4 O 14 using neutron powder diffraction experiments. The coplanar spiral magnetic structure appears below T N1 = 2.2(1) K. Values of several magnetic structure parameters change rapidly at T N2 = 1.75(5) K, indicating another phase transition, although the magnetic structures above and below T N2 are qualitatively the same. The spiral magnetic structure can be explained by frustration between nearest-neighbor and next-nearest-neighbor ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…In addition to the FM intratrimer and intertrimer interactions along the chain axis, the interchain interaction is also reasonably strong in CaNi 3 P 4 O 14 , as estimated by the first-principles calculations [26]. The consequence of the strong interchain interaction in the present CaNi 3 P 4 O 14 compound is revealed by the observed higher 3D long-range magnetic ordering temperature of T c =16 K as compared to the Mn-based compound (T N = 2.2 K) [24]. Another consequence of the stronger interchain interactions is the value of ordered moments.…”
Section: Short-range Magnetic Correlationssupporting
confidence: 67%
“…In addition to the FM intratrimer and intertrimer interactions along the chain axis, the interchain interaction is also reasonably strong in CaNi 3 P 4 O 14 , as estimated by the first-principles calculations [26]. The consequence of the strong interchain interaction in the present CaNi 3 P 4 O 14 compound is revealed by the observed higher 3D long-range magnetic ordering temperature of T c =16 K as compared to the Mn-based compound (T N = 2.2 K) [24]. Another consequence of the stronger interchain interactions is the value of ordered moments.…”
Section: Short-range Magnetic Correlationssupporting
confidence: 67%
“…30 In the Heisenberg model, frustration between nearest-neighbour (NN) and next-nearest-neighbour (NNN) exchange interactions can likewise cause a spiral structure. 31,32 An alternative explanation for a non-collinear spiral-AFM builds on the stability of the band structure. Earlier reports in Mn-based orthorhombic systems indicated that a high density of states at the Fermi surface (N(E F )) makes FM unstable while a non-collinear AFM can reduce N(E F ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, SrMn 3 P 4 O 14 has an incommensurate antiferromagnetic ground state [29] that is suppressed in the magnetic field of about 2 T giving rise to the ferrimagnetic phase on the 1/3-plateau [13]. Despite showing a very similar magnetization curve, NaFP is qualitatively different, because its ground state is ferrimagnetic already in zero field.…”
Section: Discussion and Summarymentioning
confidence: 99%